O balanço de massa controla a salinidade e a concentração de nutrientes em cultivos fertirrigados? - Silva, Gustavo Douglas Bezerra (Universidade Federal Rural do Semi-Árido, 2019)
Considering the issue involving excessive use of fertilizers in conventional farming and salinization of soils we decided to study the management of fertigation using mass balance equation. The main objective was to verify and analyze the performance of mass balance equation in the management fertigation. The study was based on papers developed from the principles of mass balance in the control of salinity levels. We selected five papers witch supported the discussions of this study. From this analyses, it was verified that the management of fertigation using the mass balance equation is efficient and guarantees the maintenance of soil salinity levels and the availability of nutrients for the crops. Key-words: Electrical conductivity. Soil salinity. Soil solution.
Artigo
Keywords: Condutividade elétrica; Salinidade do solo; Solução nutritiva; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA